2010
DOI: 10.1007/s11663-010-9360-x
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Solubility and Diffusion Coefficient of the Dissolved Alumina Species in Low-Temperature Fluoride Electrolytes

Abstract: The solubility of alumina was measured by rotating an alumina cylinder (~500 rpm) in a high-purity melt for~3 to 6 hours, crushing and sampling the frozen melt, and determining the oxygen content in a Leco analyzer. The alumina solubilities determined were as follows:(1) 3.2 ± 0.3 wt pct in NaF-AlF 3 eutectic at 1023 K (750°C); (2) 3.0 ± 0.3 wt pct in NaF-AlF 3 -CaF 2 (5 wt pct) at 1023 K (750°C); and (3) 5.2 ± 0.5 wt pct in a KF-AlF 3 eutectic at 1003 K (730°C). The alumina solubility in the KF-AlF 3 eutectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Frazer and Thonstad [19] recently showed that alumina solubility is 2 pct higher in KF-AlF 3 eutectic than in NaF-AlF 3 eutectic at about 1023 K (750°C). They suggest that an alumina slurry may not be needed in KF-AlF 3 eutectic to avoid the anode effect.…”
Section: Resultsmentioning
confidence: 99%
“…Frazer and Thonstad [19] recently showed that alumina solubility is 2 pct higher in KF-AlF 3 eutectic than in NaF-AlF 3 eutectic at about 1023 K (750°C). They suggest that an alumina slurry may not be needed in KF-AlF 3 eutectic to avoid the anode effect.…”
Section: Resultsmentioning
confidence: 99%
“…Hot AlCl3 solution is commonly used to leach cryolite based electrolyte, however, it is not a universal leaching agent for all fluoride salts. Element analysis methods such as LECO oxygen analysis [37] or inductively coupled plasma emission (ICP) [38] are also used to calculate the alumina solubility from the cooled flux. The LECO oxygen method is based on reducing the alumina in a melt sample with carbon at high temperature and calculating the alumina solubility based on the amount of carbon monoxide produced.…”
Section: Chapter 3 Alumina Solubility In the Flux Experiments Methodsmentioning
confidence: 99%
“…Similarly, Jederlinic et al raised doubts over the discussed fibrogenic capacity of gamma aluminium oxide as this low temperature range transitional form of aluminium oxide is destroyed by high temperatures used in foundry industry (approximately 960 °C) (ref. 26,39,40 ). According to Townsend et al, another problem is the fact that even in plants known for the presence of low temperature range transitional forms of aluminium oxide such as bauxite refineries, it is impossible to either accurately determine the amounts of these forms or select workers with pure exposure to them.…”
Section: Review Of Knowledge On Pulmonary Aluminosis Essential Studiesmentioning
confidence: 99%